FORMULATION AND EVALUATION OF MOUTH DISSOLVING TABLET OF MELOXICAM USING NATURAL SUPERDISINTEGRANTS - V PAWAR, CHETAN; S MUTHA, SWATI; V BHISE, SAGAR; D BORAWAKE, PAYAL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present work was the preparation and evaluation of mouth dissolving tablets (MDTs) of meloxicam using natural superdisintegrants. Methods: Meloxicam is BCS Class II (low soluble, and high permeable) drug increasing the dissolution properties of the poorly water-soluble drug meloxicam using a solid dispersion method (solvent evaporation method). Solvent evaporation method using drug and carrier as polyethylene glycol (PEG)-6000 and PEG-15,000 the ratio of 1:1, 1:2 (drug:carrier), and acetone as solvent. In house prepared banana powder were used as natural superdisintegrant. Manufacturing of MDT was done by the direct compression method. In this MDTs, various excipients were used such as mannitol used as the diluent, sodium saccharin used as a sweetening agent, Avicel pH-102 used as a binding agent, and talc and sodium lauryl sulfate (SLS) used as lubricant and glidant. The best formula of the tablet was selected according to the disintegration time (DT) and friability tests. Results: The results have shown that an increase in the meloxicam solubility was obtained using solid dispersion with the solvent evaporation method using PEG-15000 as a carrier in the ratio of 1:2 (drug:carrier). Taste masking was also done by a solid dispersion method. Tablet prepared with in house prepared banana powder gave less DT (70 s) as compared to tablet prepared with branded banana powder (80 s), but formulation F5 failed in friability testing. Improved strength of tablet obtained using SLS (<1%) also showed an increase in the dissolution performance of the tablet in formulation F6. This F6 formulation having 10% natural super disintegrating agent (in house prepared banana powder) has shown 99% cumulative drug release within 18 min. It also passed the friability test. Conclusion: Accordingly, the solubility of meloxicam was successfully enhanced through solid dispersion with carrier PEG-15,000 and formulated as a MDT to improve its oral absorption. PEG has also been used as a taste masking agent in these formulations. It was concluded that in house banana powder had excellent DT as compared to branded banana powder. Banana powder is “economical” and “easily available” than other commonly used synthetic superdisintegrants. The process of banana powder preparation is eco friendly. The meloxicam MDT formulated with natural superdisintegrant in house prepared banana powder found to pass all pharmacopeial tests.